Enriching Probiotics of Feed Using Curcuma to Increase Growth Rates of Tilapia Seeds (Oreochromis niloticus) - Atiek Pitoyo; Muhammad Akbarurrasyid; Ren Fitriadi; Lukas Giovani Gonzales Serihollo; Fajar Tri Widianto (Department of Aquaculture, 2021)
Tilapia fish (Oreochromis niloticus) is a freshwater fish commodity widely cultivated since it is both easily cultivated and in demand by consumers. The growth of tilapia is influenced by the quality of the feed. Probiotics and herbal ingredients can optimize fish growth. One example of probiotics and herbal ingredients is PHL Pro and curcuma. This study aims to determine the effect of probiotics dose of the feed on the growth rates of tilapia seeds. This research was conducted in Pangandaran Marine and Fisheries Polytechnic Campus. The study was carried out using 4 treatments and 3 replications, namely Control or without the addition of probiotics, (P1) 150ml/kg feed, (P2) 200 ml/kg feed, (P3) 250 ml/kg feed. Fish growth measured by the researchers was the average weight and total length of fish every 7 days. Based on observations of the data, it can be concluded that the provision of probiotics in the feed affected the growth rate and total length of tilapia. The optimal dose of probiotics was 150 ml/kg of feed. Based on the study results, the best treatment was P1.